2017
DOI: 10.1016/j.sapharm.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework toward identifying and analyzing challenges to the advancement of pharmacy

Abstract: The framework was found to offer valuable insight as an explanatory and diagnostic tool in policy-relevant research. By emphasizing the processual and contextual nature of reprofessionalization, the framework presents an alternative approach to traditional theories. This study also raises important questions regarding the status of pharmacy in Jordan and aims to provide guidance for local development and much-needed reprofessionalization drives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…2 Similar observations have been made by others in the Middle East. 3,4 Pharmaceutical care and the involvement of pharmacists in clinical decisions are not emphasized enough in the educational curricula and are not widely accepted or acknowledged socially in Jordan, as in most of the region. 3,5 This is attributed primarily to the pharmacy school curriculum, which is traditionally science-focused and theory-based.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Similar observations have been made by others in the Middle East. 3,4 Pharmaceutical care and the involvement of pharmacists in clinical decisions are not emphasized enough in the educational curricula and are not widely accepted or acknowledged socially in Jordan, as in most of the region. 3,5 This is attributed primarily to the pharmacy school curriculum, which is traditionally science-focused and theory-based.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Pharmaceutical care and the involvement of pharmacists in clinical decisions are not emphasized enough in the educational curricula and are not widely accepted or acknowledged socially in Jordan, as in most of the region. 3,5 This is attributed primarily to the pharmacy school curriculum, which is traditionally science-focused and theory-based. 3,5 A study published in 2008 reported that the pharmacy curricula in Jordanian universities have a significantly low number of hours allocated to pharmacology and pharmaceutical care topics, with the highest being one-fifth of the total curricular hours.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations